Studentsâ€™ Voices of Teachersâ€™ Online Written Feedback - Sa’adah, Lailatus; Anjarwati, Rosi; Romadhoni, Mohammad; Rabbianty, Eva Nikmatul (OKARA: Jurnal Bahasa dan Sastra, 2023)
Feedback should be beneficial to learners; it should provide information about their performance of a task or activity. This study aims to explore students’ concerns and expectations toward teachers’ online written feedback through photovoice. Participants involved fifteen students of a writing course. To obtain the data, a photovoice was used following Wang et al.’s SHOWeD protocols based on the theme "students’ voices on teachers’ online written feedback to promote discussion among participants and researchers about critical topics to generate solutions. Two instruments were used to collect the data; documentation in the form of the participants’ photographs and a semi-structured interview with each participant. The result revealed that students had raised some points regarding the teacher’s online written feedback. These points include: 1) online written feedback is sufficient; 2) online feedback should show the strength of students’ writing; 3) students’ revision will improve students writing quality; 4) students need a comfortable place, correct times, and snacks when revising. The study concludes that instead of simply making suggestions, as is customary when providing feedback, the students require the teacher’s assessment of their strengths. The findings suggested that teachers and lecturers should consider the points when providing online written feedback to students.